MicroRNA-221 protects myocardial contractility in myocardial ischemia/reperfusion injury through phospholamban - Hongyu Li; Jimiao Qiu; Chang Liu; Guobing Yu; Danyu Wu; Yichun Chu; Kai Wang (PLoS ONE, 2025)
Objective To investigate the effects and mechanisms of miRNA 221 on myocardial ischemia/reperfusion injury (MIRI) in mice through the regulation of phospholamban (PLB) expression. Methods The MIRI mouse model was created and mice were divided into sham, MIRI, MIRI+ 221, and MIRI+ scr groups, with miRNA 221 overexpression induced in the myocardium of MIRI mice by targeted myocardial injection. Quantitative RT-PCR analysis was performed to observe the variation in miRNA 221, PLB, SERCA2, RYR2, NCX1, Cyt C and caspase 3 mRNA levels in myocardium, while Western blot assessed the levels of PLB, p-PLB (Ser16), p-PLB (Thr17), SERCA2, RYR2, NCX1, Cyt C and caspase 3 proteins. Changes in the structural integrity of the mouse heart were identified with HE and MASSON staining, while TUNEL staining was used to evaluate the TUNEL-positive cells of cardiomyocytes. Changes in myocardium calcium concentration were detected with reagent kits and the targeting interaction between miRNA 221 and PLB was evaluated using a luciferase reporter assay. Results In the myocardium of MIRI mice, miRNA 221 level was significantly reduced, while the levels of PLB, p-PLB (Ser16), p-PLB (Thr17), and apoptosis-related genes caspase 3, and Cyt C were increased markedly, as well as calcium levels in myocardium. Following the overexpression of miRNA 221 in myocardium, there was a marked alleviation of myocardial injury and cardiomyocyte apoptosis and necrosis, significant enhancement of left ventricular systolic function, and marked decrease in the levels of PLB, p-PLB (Ser16), p-PLB (Thr17), caspase 3 and Cyt C, as well as a significant decrease in total calcium levels in myocardium. Conclusions miRNA 221 can alleviate myocardial injury in mouse myocardial ischemia/reperfusion by suppressing the expression of PLB, thus reducing calcium overload in myocardium.